Quality and stability of relationship as a function of distribution of housework, financial investments and decision making between partners - Kamenov, Željka; Jelić, Margareta; Tadinac, Meri Hromatko, Ivana (2006)
During the past few decades research has shown support for social exchange theory in intimate relationships. Satisfaction with the relationship decreased significantly for those who reported their costs and investments to be higher than the rewards gained from the relationship. Rusbult’ s investment model of close relationships predicts that the greater the investment individuals make in the relationship, less likely they are to leave, even if their satisfaction is low and other alternatives look promising. The aim of this research was to determine whether the level of personal investments and costs/rewards rate are significant predictors of the relationship quality and satisfaction with it on one side, and relationship stability on the other. As a part of 15th Psychological Summer School, a research on quality, satisfaction and stability of long-lasting intimate relationships was conducted. A total of 418 married and cohabiting couples from three Croatian regions (Zagreb, Osijek and Split) were included in a dyadic assessment. Both partners independently evaluated themselves, their partners and their relationship on a complex instrument especially designed for this research. Among other measures, participants assessed the distribution of housework, financial investments and decision making in their relationship, as well as their satisfaction with it. The satisfaction with the distribution of partners’ investments proved to be more important for the assessment of relationship quality and satisfaction than the actual investment of each partner. Satisfaction with one’ s own role in decision making proved to be the best predictor of satisfaction with the relationship and its quality for both genders, followed by satisfaction with the division of financial investments for men and satisfaction with the division of housework for women. Actual investments in a relationship were more important for its stability, especially for men. These results suggest that relationship quality and satisfaction with it can be explained with social exchange theory, whereas Rusbult’ s investment model proved to be more adequate for explaining the relationship stability.
Projekt MZOS
Projekt MZOS
ENG